2020
DOI: 10.3389/fneur.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Gilles de la Tourette Syndrome Patients With and Without Intragenic IMMP2L Deletions

Abstract: Background: Gilles de la Tourette syndrome (GTS) is a neurodevelopmental condition characterized by motor and vocal tics. The underlying etiology remains largely unknown, and GTS is considered as a complex multifactorial disorder associated with effects of several genes in combination with environmental factors. The inner mitochondrial membrane peptidase, subunit 2 (IMMP2L) has been suggested as one of the susceptibility genes for GTS, and IMMP2L-deficient mouse and human cells show increased levels of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Based on these results, it was suggested that defective cerebellar IMMP2L might play a role in GTS pathogenesis. However, analysis of various mitochondrial parameters (superoxide levels, membrane potential, mitochondrial respiratory chain) in fibroblasts from GTS patients with and without IMMP2L deletions did not detect significant changes within the analyzed groups [71]. Involvement of IMMP2L in the pathogenesis of Tourette syndrome is therefore unclear and needs further analyses, as IMMP2L deletions might have a specific effect on cells with high-energy demand, for example, neurons.…”
Section: Inner Membrane Peptidase (Imp)mentioning
confidence: 88%
“…Based on these results, it was suggested that defective cerebellar IMMP2L might play a role in GTS pathogenesis. However, analysis of various mitochondrial parameters (superoxide levels, membrane potential, mitochondrial respiratory chain) in fibroblasts from GTS patients with and without IMMP2L deletions did not detect significant changes within the analyzed groups [71]. Involvement of IMMP2L in the pathogenesis of Tourette syndrome is therefore unclear and needs further analyses, as IMMP2L deletions might have a specific effect on cells with high-energy demand, for example, neurons.…”
Section: Inner Membrane Peptidase (Imp)mentioning
confidence: 88%
“…These association studies were performed on case-control populations limited in size and need further replication. Furthermore, a study showed that deletions altering IMMP2L (encoding the mitochondrial inner membrane protease subunit 2) do not lead to a substantial mitochondrial dysfunction in fibroblasts of TS subjects, thus questioning the biological relevance of variants in this gene (Bjerregaard et al 2020). Finally, a recent study showed that socioeconomic status and education have to be taken into account when studying genetic factors involved in TS as these constitute potential confounders limiting the power of current genetic studies studies (Wendt et al 2021).…”
Section: Etiology Geneticsmentioning
confidence: 99%
“…In an animal study, the Immp2l mutation caused excessive mitochondrial superoxide generation and an increase in cellular oxidative stress [ 100 ]. However, a recent study using skin fibroblasts from patients with TS with the IMMP2L deletions revealed no evidence of substantial mitochondrial dysfunction in GTS fibroblasts [ 101 ].…”
Section: Etiologymentioning
confidence: 99%